Tsunami – Tides Interaction of the South Coast of Jember Using Delft3D-Flow - Narulita, Norma Aulia; Wiyono, Retno Utami Agung; Halik, Gusfan; Pratama, Munawir (Fakultas Teknik, Universitas Brawijaya, 2023)
The tsunami of June 3, 1994, which originated from a shift in the Indo-Australia plate, resulted in hundreds of casualties and material damage on the south coast of Jember. This study aims to understand the tidal impact of a tsunami in terms of arrival time and wave height. Several simulations of the interaction of tidal waves with tsunami waves were carried out through numerical modeling using Delft3D with modified wave characteristics from the Banyuwangi tsunami on June 3, 1994, as well as using bathymetry data from BATNAS and BIG tide data. The results of the analysis show that tidal waves can be a factor affecting the height of the tsunami waves. The increase in the amplitude of the tsunami waves was considered very local from the three observation points. This is shown at the observation locations of Puger Beach and Watu Ulo Beach, where the maximum wave amplitude occurs when the tsunami occurs independently of 7.102 m and 5.56 m, while at the Tanjung Pelindu observation location, the highest amplitude occurs when the tsunami meets the tides during low tide phase, which is 3.68 m. This research is expected to provide a basic understanding of the dynamic impact of the tidal wave when a tsunami occurs.